Career development and the importance of communication skills in a global context / Amalia Qistina Castaneda Abdullah - Abdullah, Amalia Qistina Castaneda (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Collaborative teaching can be defined as "two or more people sharing responsibility for educating some or all of the students in a classroom" (Villa, Thousand & Nevin, 2008, p. 5). APB UiTM Negeri Sembilan Kuala Pilah branch did an international webinar with Jane Mendita from Toronto, Canada last 19 April 2021 at 10am-12pm via WebEx and Facebook live. Our target audiences were ELC590 and ELC650 students. This webinar has pushed the boundaries in teaching; what was not thought of before the pandemic is now part of our new teaching norm. By collaborating with international lecturers, we could create a "school without walls" at the international level.